Acupuncture Modulates the Cerebello-Thalamo-Cortical Circuit and Cognitive Brain Regions in Patients of Parkinson's Disease With Tremor - Li, Zhe; Chen, Jun; Cheng, Jianbo; Huang, Sicong; Hu, Yingyu; Wu, Yijuan; Li, Guihua; Liu, Bo; Liu, Xian; Guo, Wenyuan; Huang, Shuxuan; Zhou, Miaomiao; et al. (Frontiers in Aging Neuroscience, 2018)
Objective: To investigate the effect of acupuncture on Parkinson’s disease (PD) patients with tremor and its potential neuromechanism by functional magnetic resonance imaging (fMRI). Methods: Forty-one PD patients with tremor were randomly assigned to true acupuncture group (TAG, n=14), sham acupuncture group (SAG, n=14) and waiting group (WG, n=13). All patients received levodopa for 12 weeks. Patients in TAG were acupunctured on DU20, GB20 and the Chorea-Tremor Controlled Zone, and patients in SAG accepted sham acupuncture, while patients in WG received no acupuncture treatment until 12 weeks after the course was ended. The UPDRS Ⅱ and Ⅲ subscales, and fMRI scans of the patients’ brains were obtained before and after the treatment course. UPDRS Ⅱ and Ⅲ scores were analyzed by SPSS, while the degree centrality (DC), regional homogeneity (ReHo) and amplitude low-frequency fluctuation (ALFF) were determined by REST. Results: Acupuncture improved the UPDRS Ⅱ and Ⅲ scores in PD patients with tremor without placebo effect, only in tremor score. Acupuncture had specific effects on the cerebrocerebellar pathways as shown by the decreased DC and ReHo and increased ALFF values, and nonspecific effects on the spinocerebellar pathways as shown by the increased ReHo and ALFF values (P<0.05, AlphaSim corrected). Increased ReHo values were observed within the thalamus and motor cortex of the PD patients (P<0.05, AlphaSim corrected). In addition, the default mode network (DMN), visual areas and insula were activated by the acupuncture with increased DC, ReHo and (or) ALFF, while the prefrontal cortex (PFC) presented a significant decrease in ReHo and ALFF values after acupuncture (P<0.05, AlphaSim corrected). Conclusions: The cerebellum, thalamus and motor cortex, which are connected to the cerebello-thalamo-cortical (CTC) circuit, were modulated by the acupuncture stimulation to alleviate the PD tremor. The regulation of neural activity within the cognitive brain regions (the DMN, visual areas, insula and PFC) together with CTC circuit may contributes to enhancing movement and improving patients’ daily life activities.